The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1124/mol.59.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, Expression, and Pharmacological Characterization of a Novel Human Histamine Receptor

Abstract: Using a genomics-based reverse pharmacological approach for screening orphan G-protein coupled receptors, we have identified and cloned a novel high-affinity histamine receptor. This receptor, termed AXOR35, is most closely related to the H3 histamine receptor, sharing 37% protein sequence identity. A multiple responsive element/cyclic AMP-responsive element-luciferase reporter assay was used to identify histamine as a ligand for AXOR35. When transfected into human embryonic kidney 293 cells, the AXOR35 recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
328
3
11

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(352 citation statements)
references
References 25 publications
10
328
3
11
Order By: Relevance
“…Similarly, by altering the lipid environment, apoE deficiency may reduce the total number of H 3 receptor binding sites available for ligand binding in the amygdala, hippocampus, and cortex. Recently, the H 4 receptor was cloned and characterized (Nakamura et al, 2000;Oda et al, 2000;Liu et al, 2001;Morse et al, 2001;Nguyen et al, 2001;Zhu et al, 2001). To determine whether H 4 signaling was involved in the observed effects on object recognition, we tested mice treated with the H 4 receptor agonist and H 3 receptor antagonist clobenpropit (Oda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, by altering the lipid environment, apoE deficiency may reduce the total number of H 3 receptor binding sites available for ligand binding in the amygdala, hippocampus, and cortex. Recently, the H 4 receptor was cloned and characterized (Nakamura et al, 2000;Oda et al, 2000;Liu et al, 2001;Morse et al, 2001;Nguyen et al, 2001;Zhu et al, 2001). To determine whether H 4 signaling was involved in the observed effects on object recognition, we tested mice treated with the H 4 receptor agonist and H 3 receptor antagonist clobenpropit (Oda et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type and Apoe -/-mice (3-5 months old) received saline, thioperamide, or clobenpropit during the training (day 4) and retention (day 5) sessions. The recently cloned H 4 receptor (Oda et al, 2000;Liu et al, 2001;Morse et al, 2001;Nguyen et al, 2001;Zhu et al, 2001) was found to have an affinity for H 3 -specific ligands. To rule out the possible contribution of the H 4 receptor to the effects of thioperamide, we also treated wild-type and Apoe -/-mice with clobenpropit, None of the differences between wild-type and Apoe -/-mice were significant.…”
Section: Effects Of H 3 Ligands On Novel Object Recognition In Wild-tmentioning
confidence: 99%
“…Il est exprimĂ© dans les fibres nerveuses et sa stimulation par l'histamine diminue la libĂ©ration d'histamine mais aussi d'autres neuromĂ©diateurs [15]. L'activation du rĂ©cepteur H4, exprimĂ© par les cellules mononuclĂ©Ă©es et les lymphocytes T CD4 + et CD8 + [16], inhibe la production de la chimiokine CCL2 engendrant ainsi une rĂ©duction du recrutement des monocytes [17]. L'histamine fait l'objet de recherches intenses et son Ă©tude est capitale pour mieux comprendre et traiter l'allergie.…”
unclassified
“…The negligible activity of CC12 at H 1 and H 2 receptors is consistent with this conclusion. At H 4 receptors, both improgan (Zhu et al, 2001) and CC12 have low affinity. The affinity of CC12 for the H 3 receptor is noteworthy (K i = 50 nM), and consistent with H 3 pharmacophore studies (Esbenshade et al, 2006).…”
Section: Discussionmentioning
confidence: 99%